Release behavior and generation kinetics of gas product during rice husk pyrolysis in a micro spouted bed reactor. (1st March 2021) - Hu, Dandan; Zeng, Xi; Wang, Fang; Han, Zhennan; Ding, Fu; Yue, Junrong; Xu, Guangwen
Highlights: A micro spouted bed was adopted for biomass pyrolysis. Release behavior and generation of main gas component were analyzed. The feasibility of spouted bed in fast reaction analysis was fully verified. Abstract: A micro spouted bed reactor was designed to implement the real-time analysis of fast reactions like biomass pyrolysis. The release characteristics of major gas components from pyrolysis, such as H2, CO, CO2, and CH4, were online recorded and comprehensively analyzed to get the generation kinetics. With the increase of pyrolysis temperature, the reaction time gradually decreased, and the recorded reaction-completion time was 3 s at 1173 K, which was much shorter than the results in literature. The calculated activation energy ( E ) for the formation of H2, CH4, CO, and CO2 were about 44.24, 27.46, 23.35, and 15.94 kJ/mol, respectively. They were more or less high than those obtained in a micro fluidized bed with the same inner diameter. By comparing with the researches in literature, it well demonstrated that the micro spouted bed granted unique heat and mass transfer, low gas back-mixing, and good feasibility in the measurement of fast reaction characterization.